2017
DOI: 10.1002/pmic.201700037
|View full text |Cite
|
Sign up to set email alerts
|

Comparative proteomic analysis of trophoblast cell models reveals their differential phenotypes, potential uses, and limitations

Abstract: Trophoblastic cell lines are widely used in in vitro studies of placental function as a surrogate for primary trophoblasts. To date, no reference proteomics dataset exists to directly compare the shared and unique characteristics of these cells. Here, we performed comparative proteomic profiling of the BeWo and HTR8/SVneo cell lines using label-free quantitative mass spectrometry. 1557 proteins were identified, which included 338 uniquely attributed to BeWo cells, and a further 304 specifically identified in H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 26 publications
1
11
0
Order By: Relevance
“…In total, 1192 bovine proteins were identified and quantified. This number of identified and quantified proteins is comparable to that in other studies in trophoblastic cell lines [12]. We also identified and quantified 334 N. caninum proteins.…”
Section: Neospora Caninum and Bovine Trophoblast Cell Proteomessupporting
confidence: 83%
“…In total, 1192 bovine proteins were identified and quantified. This number of identified and quantified proteins is comparable to that in other studies in trophoblastic cell lines [12]. We also identified and quantified 334 N. caninum proteins.…”
Section: Neospora Caninum and Bovine Trophoblast Cell Proteomessupporting
confidence: 83%
“…Multiple studies have reported that HTR-8/SVneo cells retain key functional characteristics of extravillous trophoblasts such as invasive and proliferative capacities which change in response to stress and oxygen availability, expression of adhesion molecules and a mesenchymal proteomic phenotype (Kilburn et al , 2000; Hannan et al , 2010; Liu et al , 2016a; Szklanna et al , 2017). In addition, several studies have also shown that HTR-8/SVneo cells express specific markers that uniquely identify extravillous trophoblasts including cytokeratin 7 (CK7) and α5β1 integrin, and when grown on matrigel, histocompatibility antigen, class I, G (HLA-G) (Irving et al , 1995; Kilburn et al , 2000; Khan et al , 2011; Takao et al , 2011).…”
Section: Resultsmentioning
confidence: 99%
“…The complex is important for early embryo development and preimplantation in pigs and mice 107,108 . ARPC2 expression has been identified in the BeWo trophoblastic cell line used to investigate placental function 109 and is subject to RNA editing in placentas associated with intrauterine growth restriction/small for gestational age (SGA) 110 . Overall, genes associated with the variant rs10932774 ( PNKD, TMBIM1 and ARPC2 ) show long-term evolutionary conservation consistent with a signature of balancing selection and prior research suggests links to pregnancy through a variety of mechanisms.…”
Section: Resultsmentioning
confidence: 99%